Técnicas de la terapia racional emotiva conductual para prevenir los comportamientos agresivos en estudiantes del séptimo año paralelo A, de la escuela de educación básica Miguel Riofrío nº 2, período 2014-2015 - Ramos Arias, Eduardo Andrés (2016)
Aggressive behaviors have become a relational phenomenon, affecting coexistence, personal development, levels: academic, social, family, requiring early intervention to prevent psychological problems and social future. This research aims to implement a program based on the Techniques of the Rational Emotive Behavior Therapy, to prevent aggressive behavior. Descriptive cross-sectional study, quasi-experimental design; it was supported by methods: deductive, inductive, historic, descriptive, logical, comprehensive, diagnosis, statistic; a survey Scale Violent Conduct at School (2003) and Aggression Questionnaire AQ the Buss and Perry (1992), applied to a sample of 28 students a parallel seventh year of the School of Basic Education Miguel Riofrío. No. 2. Results 82,14% expressed anger at average levels (pre-test), after applying the Psychoeducational Program decreases the percentage of students with manifestations of anger is that 35,71% (post-test), the Psychoeducational Program positive correlation was low r(x y) =0,48, it concludes that most students manifestations of anger present in high percentage, the Psychoeducational Program it managed to reduce overall aggressive behavior, improving self-control of anger; the correlation between the two variables (pre-test and post-test) was low positive